2014
DOI: 10.1155/2014/894103
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Soil Quality Status of Mt. Cameroon Soils

Abstract: The concentrations of Cu, Co, Zn, Ni, V, and Cr in topsoils at six sites located along the lower slopes of Mt. Cameroon were assessed for their potential toxicity to humans and the ecosystem. Soils were collected from horizons down to a depth of 70 cm and analysed for trace element concentration by ICP-MS technique. The Dutch soil quality standards which use %clay/silt and organic matter content to derive target values were used to assess the contamination levels of the soils. The content of these soils was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…Although other studies around Mt. Cameroon postulated anomalous concentrations of arsenic in water on the plains of the leeward side of Mount Cameroon [2] and another determined high concentrations in the soils [3] on the windward side of Mt. Cameroon respectively, this study has found no anomalous concentration of any trace metal in the groundwater.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Although other studies around Mt. Cameroon postulated anomalous concentrations of arsenic in water on the plains of the leeward side of Mount Cameroon [2] and another determined high concentrations in the soils [3] on the windward side of Mt. Cameroon respectively, this study has found no anomalous concentration of any trace metal in the groundwater.…”
Section: Discussioncontrasting
confidence: 77%
“…Thus a plethora of health risks associated with elevated trace metals concentrations in groundwater and soils around Mt. Cameroon respectively would arise if the trace metal concentrations of groundwater in this area is high [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that established levels of vanadium above threshold includes, Rasheed et al [50] reported 490 µg/g, Jayawardana et al gave 820 µg/g [51], and Hernandez and Rodriguez stated 645 µg/g of vanadium accordingly [52]. Manga et al stated 654 µg/g [53] Kabata-Pendias wrote 460 µg/g as highest vanadium level in metal soil investigation studied. [54].…”
Section: Statistical Data Analysismentioning
confidence: 97%
“…The exact locations of the fields are presented in Table 1. The study area (Fako division) has humid tropical climatic conditions and rich volcanic soils with two distinctive seasons, a long rainy season which ranges from midMarch to mid-November and a short four-month dry season expanding from mid-November to mid-March [21,22]. In cocoa farms the main source of organic waste is the cocoa pod husk which is left in the fields after bean harvest.…”
Section: Site Descriptionmentioning
confidence: 99%